2020
DOI: 10.1186/s43163-020-00012-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight on static and dynamic posturography

Abstract: Background: Postural balance is important to allow us to maintain the daily life. Poor postural response and reduced motor activity were shown to be most prominent among obese persons than in non-obese. It is found that obese elderly groups show a high prevalence of fall and supposed that adipose tissue distribution may be considered as a major factor to balance problems. In this research, we studied computerized dynamic posturography (CDP) static and dynamic tests among healthy adults according to their BMI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…They found that directional control scores drop when BMI rises. Emara et al, 2020, concluded that increased body weight affects the balance function of the normal individual, and that might be assessed by dynamic posturography [30].…”
Section: Variablesmentioning
confidence: 99%
“…They found that directional control scores drop when BMI rises. Emara et al, 2020, concluded that increased body weight affects the balance function of the normal individual, and that might be assessed by dynamic posturography [30].…”
Section: Variablesmentioning
confidence: 99%
“…Obese older people have a greater ability to fall, according to Fjeldstad et al, and the distribution of adipose tissue could have been a key contributor to balancing issues. Being overweight can have an impact on postural regulation, as evidenced by postural sway and motor reaction time (Afaf Emara et al,2020). After reducing weight, obese and morbidly obese men's postural control (i.e., COP swaying speed and extent of anteroposterior and lateral displacement) enhanced, according to some researchers (Camila Pereira et al,2017).…”
Section: Introductionmentioning
confidence: 99%
“…Postural equilibrium is required for us to function normally in our daily lives. The ability to manage the centre of mass inside the base of support, which serves to maintain the body in balance, is characterized as equilibrium (Afaf Emara et al,2020) Balance can be defined as the process that maintains the center of gravity within the body's support base and requires constant adjustments that are provided by muscular activity and joint positioning. Balance is described as the process of maintaining the body's center of gravity within its support base, which necessitates regular modifications given by muscle activity and joint alignment (Nazia et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Computerized dynamic posturography is the only approved method proven through studies which are carried out in order to establish isolated functional contributions of vestibular, visual, and somatosensory inputs necessary for posture and balance control, and central mechanisms where the integration of these inputs is realized, and the musculoskeletal system performing motor movements [Shepard, and Telian, 1996;Springhetti, and Villani, 2018;Emara et al, 2020]. Ice hockey is a fast and dynamic sport [Čech, 2015].…”
Section: Introductionmentioning
confidence: 99%